2019
DOI: 10.1080/17483107.2019.1646821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of assistive technology for students with reading and writing disabilities

Abstract: Background: Assistive technology has been used to mitigate reading disabilities for almost three decades, and tablets with text-to-speech and speech-to-text apps have been introduced in recent years to scaffold reading and writing. Few scientifically rigorous studies, however, have investigated the benefits of this technology. Purpose: The aim was to explore the effects of assistive technology for students with severe reading disabilities. Method: This study included 149 participants. The intervention group re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 33 publications
2
34
0
4
Order By: Relevance
“…As such, the many opportunities to interact with texts, using TTS-or STT functions, were perceived to have the desired effect on the continuation of student development of for example syntactic knowledge and vocabulary access and growth. These findings translated to the results from the main study [1], which showed that the intervention students did not fall behind the controls on reading measures. However, although, even if these initial explorative results are promising, further studies are needed to determine if, and how AT can be used for the development of the skills needed for text comprehension and text production, as well as how to align assistive technology app usage into the general classroom teaching of written language skills.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…As such, the many opportunities to interact with texts, using TTS-or STT functions, were perceived to have the desired effect on the continuation of student development of for example syntactic knowledge and vocabulary access and growth. These findings translated to the results from the main study [1], which showed that the intervention students did not fall behind the controls on reading measures. However, although, even if these initial explorative results are promising, further studies are needed to determine if, and how AT can be used for the development of the skills needed for text comprehension and text production, as well as how to align assistive technology app usage into the general classroom teaching of written language skills.…”
Section: Discussionsupporting
confidence: 68%
“…In line with these recommendations, and from other guidelines and conclusions of AT-usage [1,16,28], the present study explored how the students who participated in the AT-intervention were perceived to be affected, in terms of to what extent the technology enabled the user to assimilate and to communicate text using TTS and STT-functions. The study also explored how AT were perceived to impact motivation and independence for textbased learning and schoolwork in general.…”
Section: One Definition Of At Is Provided By Iso (2011)mentioning
confidence: 84%
See 3 more Smart Citations